Draft Annual Plan 2011-2012 Volume-I - Planning Commission (Planning Commission, 2011)
The State of Sikkim, nestled in the Himalayas, is a tourists. paradise. It has a total area of 7,096 sq. km extending over 112 km from North to South and 64 km from East to West. It shares a 200 km border with Tibet, a 33 km border with Bhutan and an 85 km border with Nepal. It is bounded by the vast stretches of the Tibetan Plateau in the North; the Chumbi Valley of Tibet and the Kingdom of Bhutan in the East; the Kingdom of Nepal in the West and the Darjeeling District of West Bengal in the South. It is a land of exceptional natural beauty with high mountain peaks, passes, rivers, lakes, glaciers and hot springs.
Development Planning, Economic Reforms and North-Eastern Council Affairs Department Government of Sikkim